Involvement of Total Antioxidant Activity and eNOS Gene rs1799983/ rs2070744 Polymorphisms in Breast Carcinogenesis - Hade, Istikrar M.; Al-Khafaji, Ahmed S. K.; Lafta, Fadhel M. (Iraqi Journal of Science, 2024)
Globally, breast cancer is the common malignancy affecting women and understanding its associated molecular events could help in disease prevention and management strategies. The present study was set to investigate an association between total antioxidant capacity (TAC) and endothelial nitric oxide synthase (eNOS) polymorphisms with breast cancer. For this purpose, 100 subjects were participated in this work, including 50 female patients diagnosed with breast cancer recruited from Oncology hospital, Baghdad - Iraq and 50 healthy women as a control group. The concentration of antioxidants was measured in the serums collected from blood samples of breast cancer patients and healthy controls. While eNOS SNPs (rs1799983, G894T and rs2070744, T 786C) were assessed using TaqMan SNP genotyping and utilising genomic DNA extracted from the participants. The results showed that the antioxidants levels were significantly (P˂0.0001) reduced in blood samples of breast cancer patients in comparison to that of that healthy controls (0.144± 0.097 and 0.587±0.239 respectively). Additionally, the homozygous GG genotype G894T (rs1799983) could retain beneficial impact for the protection from breast cancer potential. While SNP genotyping results showed that both of the homozygous CC and heterozygous TC genotypes (rs2070744 T >C SNP) seem to contribute to the susceptibility of breast cancer development in the investigated set of patients. Overall, the present study findings suggest an association between reduced antioxidant capacity and eNOS gene polymorphisms in breast carcinogenesis.